2006
DOI: 10.1097/00024720-200608000-00004
|View full text |Cite
|
Sign up to set email alerts
|

???Normal??? Prevertebral Soft Tissue Swelling Following Elective Anterior Cervical Decompression and Fusion

Abstract: The "normal" range for PSTS at 2 weeks and at 6 weeks after elective 1- and 2- level anterior cervical decompression and fusions is described. Our data demonstrates that edema persists at the 2-week follow-up. By 6 weeks postoperative, the increased PSTS has greatly dissipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…7 Prevertebral soft-tissue thickness was determined by measuring the thickness of soft tissue from the anterior aspect of C3-7 vertebral bodies to the posterior aspect of the trachea. 1,35,42 Magnification effects were corrected for by using the Zero-P implant as a standard reference. Radiographic fusion was defined by the presence of bony bridging across the intervertebral space on CT imaging or as less than 4° of motion on dynamic radiographs.…”
Section: Radiological Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Prevertebral soft-tissue thickness was determined by measuring the thickness of soft tissue from the anterior aspect of C3-7 vertebral bodies to the posterior aspect of the trachea. 1,35,42 Magnification effects were corrected for by using the Zero-P implant as a standard reference. Radiographic fusion was defined by the presence of bony bridging across the intervertebral space on CT imaging or as less than 4° of motion on dynamic radiographs.…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…Edema of the prevertebral soft tissue is routinely observed after ACDF. 35 A study by Suk et al identified the natural course of prevertebral soft-tissue swelling in the immediate postoperative period, with peak swelling noted at postoperative Day 2 or 3 and a gradual decrease starting at postoperative Day 4. 42 A retrospective study of 100 patients who underwent ACDF compared prevertebral soft-tissue measurements from preoperation, 2 weeks postoperation, and 6 weeks postoperation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Andrew and Sidhu [1] measured PSTS across all cervical vertebrae from C2 till the T1 level. One measurement was made at C2 and three measurements were made per cervical vertebra in the subaxial spine at the level of the superior end plate, mid body and inferior end plate.…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiographs are not helpful in determining whether a patient may be extubated because significant prevertebral swelling may be present in asymptomatic patients following anterior cervical spinal surgery. 2,48 Inspection of the upper airway should reveal an absence of edema. The performance of a cuff leak test is an important part of the process and at this time a 200-ml leak is considered the minimal amount to extubate.…”
Section: Discussionmentioning
confidence: 99%